Unveiling the Defenses: A Current and Comprehensive Review of Coleoptera Carabidae Strategies - Teresa Bonacci (Biology, 2025)
The Carabidae family, or ground beetles, is a wide and ecologically significant group within the Coleoptera order, known for its role as natural predators of agricultural pests and as bioindicators of ecosystem health. These beetles employ a variety of behavioral, morphological, and chemical defense strategies to protect themselves from predators. These mechanisms include gregariousness, stridulation, regurgitation, and chemical defenses, such as the secretion of irritating compounds from specialized glands. The defensive strategies of carabids are classified into passive and active systems, each with varying energetic costs. Chemical substances (e.g., Formic acid, Methacrylic acid, Tiglic acid, Ethacrilic acid, Isovaleric acid, Salicylaldehyde, 1,4-Benzoquinone, Toluquinone, 13-2Kt tridecan-2-one, Undecane, Tridecane, Pentadecane, M-cresol) are particularly important, as they serve to deter predators and combat pathogens like bacteria and fungi. Ground beetles utilize both polar and non-polar compounds in their defense, all contributing to their ecological success. This review explores the array of defensive mechanisms in the Carabidae family, highlighting experimental studies, field observations, and reviews published over the last five decades. The aim is to provide a comprehensive understanding of how these strategies enhance the survival and fitness of carabid beetles in their natural environments.